2001
DOI: 10.1063/1.1376155
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an all-oxide thermoelectric power generator

Abstract: An oxide thermoelectric device was fabricated using Gd-doped Ca3Co4O9 p-type legs and La-doped CaMnO3 n-type legs on a fin. The power factors of p legs and n legs were 4.8×10−4 Wm−1 K−2 and 2.2×10−4 Wm−1 K−2 at 700 °C in air, respectively. With eight p–n couples the device generated an output power of 63.5 mW under the thermal condition of hot side temperature Th=773 °C and a temperature difference ΔT=390 °C. This device proved to be operable for more than two weeks in air showing high durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(81 citation statements)
references
References 24 publications
3
78
0
Order By: Relevance
“…The simplest design of TEG consists of a p-leg and n-leg connected by conducting strips in series and covered by ceramic plate with heat conduction in perpendicular. Matsubara et al [112] reported that a fin-type-oxide thermoelectric device was fabricated by using Ca 2.75 Gd 0.25 Co 4 O 9 as p-leg and Ca 0.92 La 0.08 MnO 3 as n-leg. The high power density of the TE device was achieved at 21 mW/cm 2 at ΔT = 390 K. This high performance was observed in oxide-based thermoelectric generators, because the power factor of both p-and n-type materials increased with temperature, with no bipolar effect observed.…”
Section: In 2 O 3 -Basedmentioning
confidence: 99%
“…The simplest design of TEG consists of a p-leg and n-leg connected by conducting strips in series and covered by ceramic plate with heat conduction in perpendicular. Matsubara et al [112] reported that a fin-type-oxide thermoelectric device was fabricated by using Ca 2.75 Gd 0.25 Co 4 O 9 as p-leg and Ca 0.92 La 0.08 MnO 3 as n-leg. The high power density of the TE device was achieved at 21 mW/cm 2 at ΔT = 390 K. This high performance was observed in oxide-based thermoelectric generators, because the power factor of both p-and n-type materials increased with temperature, with no bipolar effect observed.…”
Section: In 2 O 3 -Basedmentioning
confidence: 99%
“…To improve the thermoelectric properties of polycrystalline bulks, grain texturing has been considered to be effective: Matsubara et al 11 fabricated a grain-aligned bulk sample of ͓͑Ca, Bi͒ 2 CoO 3− ͔ 0.62 CoO 2 through uniaxial pressure sintering to yield ZT = 0.29 at 700°C, being much higher than those for conventionally sintered samples. Xu et al 12 also reported an excellent TE performance ͑ZT = 0.32 at 730°C͒ for a Bi/ Na-substituted ͓Ca 2 CoO 3− ͔ 0.62 CoO 2 bulk with aligned grains.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, efforts have been devoted over the last 15 years to the optimization of TE properties of both n-type and p-type oxide materials. Good candidates for n-type materials include Nb-, W-, La-, Ce-, Pr-, Nd-, Sm-, Gd-, Dy-, and Ydoped SrTiO 3 [1][2][3][4][5][6][7][8][9][10][11][12][13], Nb-, La-, Nd-, Sm-, and Gd-doped Sr 2 TiO 4 , and Sr 3 Ti 2 O 7 [14], La-doped CaMnO 3 [15] or Al-, Ge-, Ni-and Co-doped ZnO [16][17][18][19][20], Ce-doped In 2 O 3 [21], Er-doped CdO [22,23], TiO 2 [24], Nb 2 O 5 [24], WO 3 [24], while for p-type materials the most promising compounds are Ca 3 Co 4 O 9 [25] with ZT ∼ 0.3 at 1000 K [26], and BiCuSeO with ZT ∼ 1.4 at 923 K. [27] Many studies have concerned doped SrTiO 3 , demonstrating the largest ZT ∼ 0.4 in SrTi 0.8 Nb 0.2 O 3 films at 1000 K [2], and ZT ∼ 0.41 in bulk Sr 1−3x/2 La x TiO 3 at 973 K. [12] Different strategies have been proposed to further increase TE efficiency. Attempts to decrease the lattice thermal conductivity κ l by atomic substitution of Sr by Ba have been envisaged but seem to negatively affect the TE performance.…”
Section: Introductionmentioning
confidence: 99%